Antioxidant and alpha amylase inhibitory activities of Fumaria officinalis and its antidiabetic potential against alloxan induced diabetes - Fatima, Saba; Akhtar, Muhammad Furqan; Ashraf, Komal Maria; Sharif, Ali; Saleem, Ammara; Akhtar, Bushra; Peerzada, Sohaib; Shabbir, Maryam; Ali, Sajid; Ashraf, Waseem (Cellular and Molecular Biology, 2019)
Fumaria officinalis belongs to family papaveraceae and is traditionally used to treat hypertension, hepatitis and diabetes. The current study was conducted to evaluate in vitro and in vivo antidiabetic activity of Fumaria officinalis. Aerial parts of the plant were sequentially extracted with n-hexane, chloroform, methanol and water. Phytochemical analysis was carried out on all extracts. Antioxidant activity was determined by 2,2-diphenyl-1-picryl hydrazyl (DPPH) inhibition method. In vitro alpha-amylase inhibitory activity was performed on all extracts by using dinitrosalicylic acid. Effect of aqueous and methanolic extracts of F. officinalis on blood glucose was evaluated in normo-glycaemic rats and alloxan induced diabetic rats. Glimepiride 0.2 mg/kg was used as standard therapy in diabetic rats. Results showed that methanolic extract exhibited the maximum percentage inhibition of DPPH (86.30%) and alpha-amylase inhibition (94.01%) at 500 µg/ml and 16 mg/ml concentration respectively. Administration in normo-glycaemic rats did not show any significant decrease in blood glucose level at 500 and 750 mg/kg dosage. Aqueous and methanolic extracts exhibited a significant hypoglycaemic effect (pË‚0.05) at all doses. A significant increase in the body weight and an improvement in liver and kidney function tests of diabetic rats were observed. These extracts also reduced the damage to the cells of glomeruli, interstitial inflammation, necrosis of tubular cells and thrombosis in the kidney, the enlargement of sinusoids and steatosis in the liver of diabetic rats. This study concludes that F. officinalis may have antidiabetic potential possibly due to its antioxidant and alpha-amylase inhibitory activities.